Design, Synthesis, and Antitumor Activity of Novel Quinazoline Derivatives - Wang, Liuchang (Molecules, 2017)
In an attempt to explore a new class of epidermal growth factor receptor (EGFR) inhibitors, novel 4-stilbenylamino quinazoline derivatives were synthesized through a Dimorth rearrangement reaction and characterized via IR, (1)H-NMR, (13)C-NMR, and HRMS. Methoxyl, methyl, halogen, and trifluoromethyl groups on stilbeneamino were detected. These synthesized compounds were evaluated for antitumor activity in vitro against eight human tumor cell lines with an MTS assay. Most synthesized compounds exhibited more potent activity (IC(50) = ~2.0 μM) than gefitinib (IC(50) > 10.0 μM) against the A431, A549, and BGC-823 cell lines. Docking methodology of compound 6c and 6i binding into the ATP site of EGFR was carried out. The results showed that fluorine and trifluoromethyl played an important role in efficient cell activity.